2021
DOI: 10.1038/s41375-021-01472-2
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-15a-5p acts as a tumor suppressor in histiocytosis by mediating CXCL10-ERK-LIN28a-let-7 axis

Abstract: Erdheim–Chester disease (ECD) is characterized by excessive production and accumulation of histiocytes within multiple tissues and organs. ECD patients harbor recurrent mutations of genes associated with the RAS/RAF/MEK/ERK signaling pathway, particularly, the BRAFV600E mutation. Following our previous finding that miR-15a-5p is the most prominently downregulated microRNA in ECD patients compared to healthy individuals, we elucidated its role in ECD pathogenesis. Bioinformatics analysis followed by a luciferas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…Bioinformatics and dual-luciferase reporter assay analyses predicted CCND1 as a target of hsa-miR-15a-5p [ 64 ]. Additionally, a recent study revealed that miR-15a-5p promotes apoptosis and inhibits cell growth through the changes in expression levels of pro-survival genes and proteins, including Bcl-xl and Bcl-2 and inhibition of oncogenic transcription factors such as CCND2, Bcl-6, MYC, and PIK3R1 [ 65 ]. It is reported that miR-15a-5p induces lung cell apoptosis by activating caspase-3/9 in a monocrotaline (MCT) rat model [ 66 ] ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics and dual-luciferase reporter assay analyses predicted CCND1 as a target of hsa-miR-15a-5p [ 64 ]. Additionally, a recent study revealed that miR-15a-5p promotes apoptosis and inhibits cell growth through the changes in expression levels of pro-survival genes and proteins, including Bcl-xl and Bcl-2 and inhibition of oncogenic transcription factors such as CCND2, Bcl-6, MYC, and PIK3R1 [ 65 ]. It is reported that miR-15a-5p induces lung cell apoptosis by activating caspase-3/9 in a monocrotaline (MCT) rat model [ 66 ] ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, miR-15a-5p might be involved in the inflammatory cascade during sepsis, potentially via the activation of the NF-κB pathway and targeting TNIP2 [ 56 ]. Overexpression of miR-15a-5p has been shown to inhibit cell growth and induce tumor cell apoptosis, primarily through the downregulation of Bcl-2 and Bcl-xl [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiRNA was reverse-transcribed with miRNA-specific stem-looped RT primers (Life Technologies, ThermoFisher Scientific Inc) and detected by quantitative reverse transcription polymerase chain reaction (qRT-PCR) as previously described. 20 …”
Section: Methodsmentioning
confidence: 99%
“…Reaction conditions for the gene expression assays were similar to the miRNA qRT-PCR described before. 20 …”
Section: Methodsmentioning
confidence: 99%